2015
DOI: 10.3109/21691401.2014.1001494
|View full text |Cite|
|
Sign up to set email alerts
|

Pretreatment with pPolyHb attenuates H2O2-induced endothelial cell injury through inhibition of JNK/p38 MAPK pathway by upregulation of heme oxygenase-1

Abstract: Polymerized porcine hemoglobin (pPolyHb) exhibits a protective effect on ischemia/reperfusion of organ grafts. A series of experiments were performed to explore the underlying cytoprotective mechanisms of pPolyHb pretreatment on H2O2-induced cell death and apoptosis. The results showed that the pretreatment augmented heme oxygenase-1 (HO-1) expression, and at the same time, decreased the phosphorylation of JNK/p38 mitogen-activated protein kinase (MAPK) and intracellular ROS generation in H2O2-treated HUVECs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Mitogen‐activated protein kinases regulate many cell physiological functions, such as cell proliferation and apoptosis, and are susceptible to stimulation by various physiological factors, including ROS 9,10,34 . Next, we explore whether the antiapoptotic effect of tCQA is related to the regulation of MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitogen‐activated protein kinases regulate many cell physiological functions, such as cell proliferation and apoptosis, and are susceptible to stimulation by various physiological factors, including ROS 9,10,34 . Next, we explore whether the antiapoptotic effect of tCQA is related to the regulation of MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…MAPKs control many physiological functions, such as cell growth, proliferation, and apoptosis. Xue 9 reported that polymerized porcine hemoglobin reduced the H 2 O 2 ‐induced endothelial cell damage by reducing the overproduction of ROS and subsequent phosphorylation of p38 MAPK; Gong 10 reported that Vaccarin prevents HUVEC inflammation and apoptosis induced by ox‐LDL by inhibiting ROS/p38 MAPK signaling. Therefore, inhibiting IR‐activated ROS/MAPK signaling pathway may be an effective strategy for the development of new radioprotective agents.…”
Section: Introductionmentioning
confidence: 99%